2016
DOI: 10.5772/63985
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Sensitive Fluorescence Aptamer Biosensors of Adenosine Triphosphate

Abstract: A fluorescence resonance energy transfer (FRET)-based aptamer biosensor (aptasensor) for sensitive determination of adenosine triphosphate (ATP) was developed. The energy donor and acceptor were 5′-carboxyfluorescein (5′-FAM) and gold nanoparticles (AuNPs), respectively. AuNPs were linked to 3′-SH-DNA by Au-S bond. This aptasensor was obtained by the hybridization between the complementary DNA strands of the 5′-FAM and AuNPs. The detecting results indicated that the FRET increase efficiency (F r) of detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The linear regression equation was fitted as y = 0.1395x + 0.0875 with a correlation coefficient of 0.996 (n = 7). The limit of detection (LOD) was evaluated to 8.5 nM at 3s blank criterion, which was comparable with previously reported aptasensors, e.g., DNA/silver nanocluster-based fluorescence light-up system (91.6 nM) (Zhu et al, 2016), gold nanoparticles-based colorimetric assay (50 nM) (Huo et al, 2016), core-shell silver@SiO 2 nanoparticles-based fluorescent aptasensor (14.2 nM) (Song et al, 2016), AuNP-based fluorescence aptasensor (15.2 nM) (Meng et al, 2016) and Zinc(II)-protoporphyrin IX/G-quadruplex-based fluorescence aptasensor (10 μM) (Zhang et al, 2012). To further elucidate the merit of using the Tb-CDs for the development of fluorescence method, the AuNP-aptamer-NaCl system without Tb-CDs was also utilized for the detection of target ATP by using UV-vis absorption spectroscopy (Fig.…”
Section: Dose Responses Of the Fluorescence Aptasensing Platform Towasupporting
confidence: 88%
“…The linear regression equation was fitted as y = 0.1395x + 0.0875 with a correlation coefficient of 0.996 (n = 7). The limit of detection (LOD) was evaluated to 8.5 nM at 3s blank criterion, which was comparable with previously reported aptasensors, e.g., DNA/silver nanocluster-based fluorescence light-up system (91.6 nM) (Zhu et al, 2016), gold nanoparticles-based colorimetric assay (50 nM) (Huo et al, 2016), core-shell silver@SiO 2 nanoparticles-based fluorescent aptasensor (14.2 nM) (Song et al, 2016), AuNP-based fluorescence aptasensor (15.2 nM) (Meng et al, 2016) and Zinc(II)-protoporphyrin IX/G-quadruplex-based fluorescence aptasensor (10 μM) (Zhang et al, 2012). To further elucidate the merit of using the Tb-CDs for the development of fluorescence method, the AuNP-aptamer-NaCl system without Tb-CDs was also utilized for the detection of target ATP by using UV-vis absorption spectroscopy (Fig.…”
Section: Dose Responses Of the Fluorescence Aptasensing Platform Towasupporting
confidence: 88%
“…For example, in a lateral flow strip format, aptamer functionalized Gold-nanoparticles (AuNPs) have shown unequivocal visual detection of down to 2.5 nM thrombin (signal/noise = 3), providing superior sensitivity and specificity relative to conventional antibody-based assays (Xu et al, 2009 ). A FRET-based aptasensor was designed by Meng et al ( 2016 ) using functionalized AuNPs as energy acceptors; their assay showed no-cross reactivity to other nucleotides and could specifically detect ATP as low as 15.2 nmol/L.…”
Section: Enhancing Aptamer Assay Parametersmentioning
confidence: 99%
“…[17] Indeed, quite a few aptamer-based fluorescent sensors have been described. [8,16,[18][19][20][21] However, these sensors generally incorporate conventional dyes that are vulnerable to fluorescence quenching when they form aggregates at overly high concentration. This phenomenon, known as 'aggregationcaused quenching' (ACQ), is a notorious issue that restricts the usefulness of conventional dyes in biomolecular applications.…”
Section: Introductionmentioning
confidence: 99%